Porosity Parameters Of Cement Stone Containing Chemical Admixtures Of Different Purpose - Lukas Venčkauskas (Mokslas: Lietuvos Ateitis, 2013)
The conducted research has established a complex influenceand the impact of separate chemical admixtures of differentpurpose on the parameters of the porosity of hardened cementpaste such as open and closed porosity, the average size of poresand the rates of pore inequality. According to the parametersof the porosity of hardened cement paste, on the basis of A. E.Sheikin’s methodology, the number of freezing-thawing cycleswas predicted. This research used plasticizing, viscosity modifyingand antifoaming admixtures. It has been found that, when theamount of plasticizing admixture in cement paste (W/C–0.45) isconstant and makes 1.1% of the cement mass, and the amountof viscosity modifying and antifoaming the admixture increasesfrom 0.1 to 0.6% and from 0.05 to 0.3% respectively, the openporosity of hardened cement paste varies between 30.21% and31.06%, while closed porosity varies between 5.39% and 6.22%.When the amount of the plasticizing admixture in cement paste(W/C–0.45) exceeds 1.1% of the cement mass, the open porosityof hardened cement paste increases by 1.4 times and closedporosity decreases by 2.5 times. While adding 0.1% of the viscositymodifying admixture to cement paste, the open porosityof hardened cement paste is increased by 1.5 times and closedporosity decreases by 2.4 times. The amount of 0.05% of thecement mass of the antifoaming admixture results in the increasedopen porosity of hardened cement paste by 1.5 times and reducedclosed porosity by 3.5 times.